2008
DOI: 10.1002/eji.200738131
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as a new player in mast cell biology

Abstract: The secreted glycoprotein osteopontin (OPN) sets into motion an astounding variety of activities that range from bone remodeling via immunomodulation to the inhibition of apoptosis. In the current issue of the European Journal of Immunology, OPN now also enters mast cell biology and the regulation of IgE-dependent immune responses since it is reported that connective tissue-type mast cells from fetal murine skin constitutively secrete biologically active OPN. Moreover, it is shown that, in vitro, OPN augments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…A similar trend for an increase in osteopontin was observed in the hearts of CeO 2 instilled C57BL/6. Osteopontin is reported to play a role in the pathogenesis of inflammatory and immune-mediated diseases (Wang and Denhardt 2008) and more recently has been identified as a novel mast cell mediator which is produced by mast cells (Bulfone-Paus and Paus 2008; Nagasaka et al 2008). Serum osteopontin levels are proposed as a biomarker for pneumoconiosis since an increase in osteopontin has been observed in asbestosis patients compared to healthy controls (Park et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend for an increase in osteopontin was observed in the hearts of CeO 2 instilled C57BL/6. Osteopontin is reported to play a role in the pathogenesis of inflammatory and immune-mediated diseases (Wang and Denhardt 2008) and more recently has been identified as a novel mast cell mediator which is produced by mast cells (Bulfone-Paus and Paus 2008; Nagasaka et al 2008). Serum osteopontin levels are proposed as a biomarker for pneumoconiosis since an increase in osteopontin has been observed in asbestosis patients compared to healthy controls (Park et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3 The overexpression of OPN has been found in a variety of human cancers such as lung cancer, breast carcinoma, esophageal cancer, endometrial cancer, gastric cancer, and malignant pleural mesothelioma. [4][5][6][7][8][9] Previously, we reported that the level of OPN mRNA expression in CRC cells or tissues was significantly higher than that in normal intestinal epithelial cell line or corresponding nontumor colon tissues.…”
Section: Introductionmentioning
confidence: 99%
“…OPN engages a number of receptors such as integrins α v and β 1, and it is also a ligand for CD44 [22, 33]. These receptors directly or indirectly activate cellular signaling pathways such as p38 MAPK, NF- κ B, and AP-1, allowing OPN to mediate cell-matrix interaction and factor production [22, 33].…”
Section: Discussionmentioning
confidence: 99%
“…These receptors directly or indirectly activate cellular signaling pathways such as p38 MAPK, NF- κ B, and AP-1, allowing OPN to mediate cell-matrix interaction and factor production [22, 33]. It is also reported that OPN production from airway cells requires the activation of transcription factors, NF- κ B and AP-1, after inflammatory stimulation [13].…”
Section: Discussionmentioning
confidence: 99%